Suffragettes’ figure in the Bogota’s magazine El Gráfico during the decade 1910-1920 - Molina-Ibañez, Brayan Eduardo (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The suffragette movement of the beginning of century XX were featured in the Bogota variety magazine El Gráfico, as a reality that was discordant with the Bogota social environment in the 1910s the above mentioned was due to the fact that society was adapting to new forms of modernity and still had a traditional perspective regarding the assets of the ladies and their role in society. In that way, this article analyzes the perspective of the suffragism present in the writing which reflect part of the considerations of the national and international scene in relation to change in female life; for which the research methodology is assumed from the perspective of cultural history, from the review and analysis of the texts published in the magazine, and which reflect part of the traditional thought of the time. Among the findings is that El Gráfico was a scene of speculation in Colombia from where aspects of the modernity of the nascent century XX moment in which were questioned changes are observed in terms of the economy, laws and social perspectives on women; it is concluded that the treatment given to the subject of suffragettes was presented as dangerous to national life, as a destabilizing scenario for the family.